Asian Studies. (Quezon City : The University of the Philippine Press, 1967)
No. 2
The colonial origins of Manila and Batavia: desultory notes on nascent metropolitan primacy and Urban systems in Southeast Asia/ Robert R. Reed. --- pp. 543-562.
The Pattern of Indonesian migration and settlement in Malaya/ Tunku Shambul Bahrin.----pp.233-257.